2021
DOI: 10.2139/ssrn.3842326
|View full text |Cite
|
Sign up to set email alerts
|

Five Facts About the Distributional Income Effects of Monetary Policy

Abstract: We use Swedish administrative individual-level data to document five facts about the distributional income effects of monetary policy. (i) The effects of monetary policy shocks are Ushaped with respect to the income distribution-i.e., expansionary shocks increase the incomes of high-and low-income individuals relative to middle-income individuals. (ii) The large effects in the bottom are accounted for by the labor-income response and (iii) those in the top by the capital-income response. (iv) The heterogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Our findings thus imply that the Federal Reserve's recent change in its conduct of monetary policy from strict to average inflation targeting will benefit the employment of female, minority, and low skilled workers. At the same time, expansionary monetary policy increases inflationary pressure and may also foster wealth inequality by raising asset prices (Amberg et al, 2021;Peydró et al, 2021). Managing the tradeoff between broad-based employment goals, inflation targets, and wealth inequality is an important topic of further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings thus imply that the Federal Reserve's recent change in its conduct of monetary policy from strict to average inflation targeting will benefit the employment of female, minority, and low skilled workers. At the same time, expansionary monetary policy increases inflationary pressure and may also foster wealth inequality by raising asset prices (Amberg et al, 2021;Peydró et al, 2021). Managing the tradeoff between broad-based employment goals, inflation targets, and wealth inequality is an important topic of further research.…”
Section: Discussionmentioning
confidence: 99%
“…We build on prior work that uses aggregate data to study the effect of monetary policy on wealth and consumption inequality (see, e.g., Romer and Romer (1999), Zavodny and Zha (2000), Thorbecke (2001), Carpenter and Rodgers III (2004), Coibion et al (2017)). In contemporaneous research, Amberg et al (2021) and Peydró et al (2021) use annual registry data from Sweden and Denmark to study the effect of monetary policy on consumption and wealth inequality. Coglianese et al (2021) use the unexpected interest hike in Sweden in 2010-2011 to show that workers with shorter tenure were more negatively affected than other workers.…”
Section: Introductionmentioning
confidence: 99%
“…To study these broader distributional effects, I use Gini indices of wealth and income for the United States over the period 1929-2010 and France over the period 1902-2010 from the World Inequality Database (WID). Because movements in the tails of the distribution may cancel each other out (Amberg et al, 2022), and because previous studies have found that tighter monetary policy does not decrease inequality along the entire income distribution (Herradi and Leroy, 2021), I expect that the impact of monetary policy on the Gini indices for income and wealth will be either smaller in magnitude or insigni cant. 9 I nd, in line with my expectations, that while tight monetary policy does decrease inequality in at least the short term, the magnitudes are less than one tenth as large for the Gini indices as they are for top percentile and decile shares.…”
Section: Gini Indicesmentioning
confidence: 93%
“…After a move towards negative rates, wealth and income inequality can also be affected directly due to the impact on asset prices (e.g., house, equity, or bond prices) or interest rates. As inequality has risen significantly in recent decades, several research papers have considered the distributional effects of monetary policy (c.f., Amberg et al, 2021;Andersen et al, 2021). To the extent that households have different balance sheets, it is natural to expect that heterogeneous asset price changes may lead to unequal changes in wealth, and could impact inequality.…”
Section: Othersmentioning
confidence: 99%